Coronary artery calcifications on breast cancer radiotherapy planning CT scans and cardiovascular risk: What do patients want to know? - Roxanne Gal; Madelijn L. Gregorowitsch; Marleen J. Emaus; Erwin LA. Blezer; Femke van der Leij; Sanne GM. van Velzen; Julia J. van Tol-Geerdink; Ivana Išgum; Helena M. Verkooijen (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2021)
Background: Coronary artery calcifications (CAC) is a strong predictor of cardiovascular disease (CVD), which can be automatically quantified on routine breast radiotherapy planning computed tomography (CT) scans. Around 8% of patients have (very) high CAC scores and corresponding increased risks of CVD. Aim: This study explores whether, how, and under what conditions women with breast cancer want to be informed about their CAC-based CVD risk. Methods: A cross-sectional survey study was conducted in a random sample of UMBRELLA, a prospective breast cancer cohort. Participants (n = 79) filled out a questionnaire about their knowledge on the CVD risk following breast cancer, their interest in being informed about their CVD risk based on CAC score, and preferences on how they would want to receive this information. Results: Most participants (66%) were not aware that the presence of CAC indicates an increased CVD risk. Participants indicated that they were not or only slightly aware of the risk of treatment-induced cardiotoxicity (48%), and that the risk of cardiotoxicity was higher in patients with pre-existing CVD risk factors (82%). The vast majority (90%) indicated that they want to be informed about in increased CAC-based CVD risk. Conclusions: The majority of patients with breast cancer wants to be informed about their CAC-based CVD risk. With the majority of patients with breast cancer undergoing radiotherapy, and with low cost and automated options for accurate CAC measurement in planning CT scans, it is important to develop strategies to manage patients with an increased CAC-based risk of CVD.